Competitiveness and Entrepreneurship, and their Effects on Economic Growth - Mohsen Mohammadi Khyareh; Nasrin Rostami (International Journal of Management, Accounting and Economics, 2018)
Entrepreneurship is the foundation of competition and innovation among firms, as well as on the national economy. In order to create a favorable environment for entrepreneurship strengthening, it must use symmetric and appropriate competitive conditions with entrepreneurship, to improve production and employment, and thereby increase economic growth. Therefore, the main objective of this study is to investigate the effects of competitiveness and entrepreneurship, which ultimately lead to economic growth. In this paper, through collecting library resources and with a descriptive approach, the interrelations between different components of competitiveness and entrepreneurship, as well as their effects on economic growth, are discussed.